Gambaran Faktor Psikososial dan Distress pada Guru Sekolah Luar Biasa (SLB) di Kota Depok saat Pandemi COVID-19 Tahun 2022 - Hafia, Azka; Erwandi, Dadan (National Journal of Occupational Health and Safety, 2022)
This study aims to obtain an overview of psychosocial factors and distress among special education teachers in Depok during the COVID-19 pandemic in 2022. This study used a cross-sectional study design with a semi-quantitative approach through filling out questionnaires and interviews. A total of 67 special education teachers in Depok participated in this study. The results showed that 34.3% of teachers experienced moderate distress, and 16.4% of teachers experienced significant distress. Then, it was found that distress is more experienced by female teachers (52.7%), aged > 30 years (52.4%), came from non-PLB study programs (52.5%), did not have personality type A (66,6%), have a working period of > 10 years (60%), are married (59.5%), have children (64.9%), have poor social support from family (89.3%), have a workload high (61.8%), have bad work equipment (63.9%), have bad working hours (64.3%), have high role conflict (73.7%), have high role ambiguity (76.2% ), have poor work control (81.4%), have poor social support from superiors and coworkers (81.4%), have a high work-home conflict (86.2%), rarely do hobbies (66 ,7%), and had a severe fear of COVID-19 infection (71.4%).